BIBLIOMETRIC ANALYSIS OF THE WORK FROM ANYWHERE TRANSFORMATION IN OPTIMIZING PUBLIC SERVICES IN THE DIGITAL ERA - Efendi, Erizal Candra; Oktaviane, Diga Putri (Jurnal Administrasi Negara, 2025)
Digital transformation has driven significant changes in work systems, including the implementation of the Work From Anywhere (WFA) concept, which enables technology-based work flexibility. This work model is not only applied in the private sector but is also being adopted in public services to improve efficiency and accessibility. However, the implementation of WFA in the public sector faces challenges such as the digital infrastructure readiness, data security, and changes in work culture. This study aims to analyze the development of research related to Work From Anywhere (WFA) in optimizing public services in the digital era through a bibliometric approach. The method used is bibliometric analysis with a quantitative technique using data from academic databases such as Scopus and Web of Science. VOSviewer software is used to map research trends, collaboration between researchers, and identify research gaps in this topic. The results show that the publication trend on Work From Anywhere (WFA) in the public sector has increased significantly since 2020, in line with the COVID-19 pandemic that encouraged remote work policies. The analyzed studies reveal that the success of WFA implementation in the public sector is highly dependent on technological readiness, flexible policies, and results-based evaluation systems. In addition, the main challenges faced are the digital divide between regions and the need for stricter regulations related to cybersecurity. In conclusion, Work From Anywhere (WFA) has significant potential to improve the effectiveness of public services if supported by appropriate regulations, adequate technological infrastructure, and human resource readiness. Therefore, an adaptive policy strategy is needed to ensure this work system can be optimally implemented without compromising the quality of public services.